Analysis of Environmental Accounting Applicationin Cattle Waste Management in Kabupaten Parigi Moutong - Tina Sintiani; Sugianto; Abdul Kahar; Ernawaty Usman (Politeknik Ganesha Medan, 2025)
This research aims to analyze the application of environmental accounting in the management of cattle waste at the Harapan Baru II Farmers Group in Kabupaten Parigi Moutong. This research uses a qualitative approach with an exploratory case study method through interviews, observations, and documentation, which are analyzed using the Miles and Huberman model. The research results show that the group has processed livestock waste into economically valuable compost fertilizer, even tho they still use manual equipment. From a cost perspective, routine expenses such as the purchase of chalk and sacks have been recorded, but have not yet been separated from other operational costs. The group has also kept simple records through cash and asset books, but these are not fully compliant with PSAK 69. Socially, waste management receives community support because it does not cause pollution and increases income, but regulatory support from the government is still limited. This finding indicates that the application of environmental accounting among smallholder farmers is already happening in practice, but it needs to be strengthened through more detailed cost separation and the implementation of appropriate accounting standards.